Nursing care plan for patients subjected to percutaneous coronary intervention - Reczek, Agata; Brzostek, Tomasz; Gabryś, Teresa; Malinowska-Lipień, Iwona; Kawalec, Ewa; Gawor, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2008)
An introduction to clinical practice of percutaneous coronary revascularization procedures (PCI) has a significant effect on the results of coronary heart disease treatment and, consequently, on the prolongation of a patient’s life and an improvement of its quality. Those procedures are of an invasive nature, whereby they are burdened with the risk of an occurrence of complications. The purpose of this paper is to present a nursing care plan for patients subjected to percutaneous coronary intervention.